Respuesta :

Answer:

x = 2, x = 8

Step-by-step explanation:

Calculate the distance using the distance formula and equate to 5

d = √ (x₂ - x₁ )² + (y₂ - y₁ )²

with (x₁, y₁ ) = A (x, - 1) and (x₂, y₂ ) = B(5, 3)

d = [tex]\sqrt{(5-x)^2+(3+1)^2}[/tex]

   = [tex]\sqrt{(5-x)^2+4^2}[/tex]

   = [tex]\sqrt{(5-x)^2+16}[/tex] , thus

[tex]\sqrt{(5-x)^2+16}[/tex] = 5 ( square both sides )

(5 - x)² + 16 = 25 ( subtract 16 from both sides )

(5 - x)² = 9 ( take the square root of both sides )

5 - x = ± [tex]\sqrt{9}[/tex] = ± 3 ( subtract 5 from both sides )

- x = - 5 ± 3 , thus

- x = - 5 + 3 = - 2 ( multiply both sides by - 1 )

x = 2

or

x = - 5 - 3 = - 8 ( multiply both sides by - 1 )

x = 8

Answer:

Step-by-step explanation:

The formula to find the distance between 2 points in the coordinate plane is

[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]

We have our distance, and we also have all the coordinates but the first x.  Fillling in with what we have gives us this:

[tex]5=\sqrt{(5-x_1)^2+(3-(-1))^2}[/tex]

which simplifies to

[tex]5=\sqrt{(5-x_1)^2+(4)^2}[/tex] . Expanding that binomial gives us:

[tex]5=\sqrt{25-10x+x^2+16}[/tex] .  Combining like terms gives us:

[tex]5=\sqrt{x^2-10x+41}[/tex] which is the same thing as above, only in standard form for polynomials. Now we need to get that x out from under that square root sign. We do that by squaring both sides to get:

[tex]25=x^2-10x+41[/tex] . Now we have to factor to solve for x. We'll put everything on one side of the equals sign, set the polynomial equal to 0, then factor.

[tex]0=x^2-10x+16[/tex] is our polynomial now. a = 1, b = -10, c = 16. The product ac is 1 * 16 which is 16. Some combination of the factors of 16 will result in a -10. So we need the factors of 16.

16: {1, 16}, {2, 8}, {4, 4}

The only combination of those factors that will result in a -10 is the second pair, {2, 8}. If we add 2 and 8 we get 10, but in order for our 10 to be negative, both 2 and 8 have to be negative. So we rewrite the polynomial in terms of -2 and -8:

[tex]0=x^2-8x-2x+16[/tex]

Now we can factor by grouping. Group the first 2 terms together and the second 2 terms together without moving any of their positions:

[tex]0=(x^2-8x)-(2x+16)[/tex]

From each set of parenthesis we will now factor out what's common.  x is common in the first set of ( ), and 2 is common in the second set of ( ):

[tex]0=x(x-8)-2(x-8)[/tex]

What's common now is the binomial (x - 8). So we'll factor that out now:

[tex]0=(x-8)(x-2)[/tex]

By the Zero Product Property, either

x - 8 = 0 or x - 2 = 0.

If x - 8 = 0, then x = 8. If x - 2 = 0, then x = 2.

It looks like we have 2 solutions. Let's try them both and see if, when we stick an 8 and then a 2 into our distance formula, the distance is 5:

[tex]d=\sqrt{(5-8)^2+(4^2)}[/tex] is

[tex]d=\sqrt{(-3)^2+(4)^2}[/tex] is

[tex]d=\sqrt{9+16}[/tex] is

[tex]d=\sqrt{25}[/tex] which does in fact equal 5. Now let's try the 2:

[tex]d=\sqrt{(5-2)^2+(4)^2}[/tex] which is

[tex]d=\sqrt{(3)^2+(4)^2}[/tex] is

[tex]d=\sqrt{9+16}[/tex] is

[tex]d=\sqrt{25}[/tex] which also comes out to equal 5.

So the 2 values of x which will work here are 2 and 8.

ACCESS MORE